South Caucasus and Central Asia - The Belt and Road Initiative : Armenia Country Case Study - World Bank (World Bank, Washington, DC, 2020)
Armenia is a small land-locked mountainous country with relatively difficult access to regional and global markets. The borders with Azerbaijan in the east and with Turkey in the southwest and west are closed. Only the borders with Georgia in the north and Iran in the south are open for trade and transport. Roads dominate its mode of transportation because of its mostly mountainous terrain. The only cross-border rail connection is through Georgia. None of the BRI-corridors pass through the country and even the one that goes through Georgia is only accessible in the western direction. This note assesses the potential impact of BRI over connectivity and the Armenian economy. It looks at how, if fully implemented globally, the BRI is expected to achieve better transport connections and greater economic integration, discusses improvements in Armenia’s cross-border transport, electricity and ICT infrastructure to-date, and the potential impact of the completion of BRI transport projects on lowering Armenian shipment time. It further looks at the likely economic impact of BRI-related reductions in shipment time on exports, FDI and GDP, the within-country regional distribution of that impact and how complementary polices can enhance the positive impact, mitigate risks and reduce regional inequity. Finally, it also examines the fiscal risk of scaling-up investment in BRI projects in the coming years without undermining medium-term debt sustainability.